Sexual politics and feminist science : women sexologists in Germany, 1900-1933 - Leng, Kirsten, 1979- (Signale (Ithaca, N.Y.), 2017)
In Sexual Politics and Feminist Science, Kirsten Leng restores the work of female sexologists to the forefront of the history of sexology. While male researchers who led the practice of early-twentieth-century sexology viewed women and their ...